Applied unsupervised learning with Python discover hidden patterns and relationships in unstructured data with Python - Johnston, Benjamin (Computer scientist) (Packt Publishing, 2019)
Starting with the basics, Applied Unsupervised Learning with Python explains various techniques that you can apply to your data using the powerful Python libraries so that your unlabeled data reveals solutions to all your business questions.